Hernia of umbilical cord containing an accessory liver lobe and the gallbladder: A case report - Takwa Mili; Yosra Ben Ahmed; Ahmed Ben Younes; Awatef charieg; Maryem Marzouki; Intissar Chibani; Faouzi Nouira; Said Jlidi (Elsevier, 2023)
Introduction: Distinguishing an omphalocele from a hernia of the umbilical cord (HUC) can be a significant clinical challenge. Abdominal organ incarceration is an extremely uncommon complication of HUC. We report a case of a HUC containing an accessory liver lobe with embedded gallbladder. This case provides an opportunity to review the surgical management of this condition in consideration of its possible complications. Case presentation: We present the case of a 1-day-old male phenotype neonate who was referred to our department with a diagnosis of omphalocele. The clinical impression was an umbilical cord hernia. In Surgical exploration, the gallbladder was found inside the sac embedded in an accessory liver lobe. We performed cholecystectomy with resection of the liver lobe. Postoperative course was uneventful. Conclusion: Incarcerated gallbladder or accessory liver lobe are unusual in HUC. Resection seems to be the procedure of choice due to the risk of torsion, inflammation, and volvulus.